2012
DOI: 10.1111/j.1939-9162.2012.00061.x
|View full text |Cite
|
Sign up to set email alerts
|

Reelection and Legislative Power: Surprising Results from Brazil

Abstract: A diverse and growing literature ties legislative professionalization and power to career paths. In particular, higher rates of reelection and longer legislative careers should produce more professional, competent, and high‐quality legislatures. Legislators have more incentives to strengthen their own institution when they intend to remain there for a long career. Using data from the most recent constitutional convention in Brazil, we show that legislators with greater prospects for long careers were actually … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
21

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 30 publications
0
7
0
21
Order By: Relevance
“…With respect to the first point, we stress the importance of understanding legislators' alternatives. Even when a legislative seat is not particularly valuable, re‐election rates might be relatively high if legislators have little chance of obtaining a better office, as is the case in Brazil (Cunow et al ; Pereira and Rennó ). Indeed, our results indicate that much like their Brazilian counterparts, Argentine legislators only seek re‐election when they cannot afford a better alternative.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to the first point, we stress the importance of understanding legislators' alternatives. Even when a legislative seat is not particularly valuable, re‐election rates might be relatively high if legislators have little chance of obtaining a better office, as is the case in Brazil (Cunow et al ; Pereira and Rennó ). Indeed, our results indicate that much like their Brazilian counterparts, Argentine legislators only seek re‐election when they cannot afford a better alternative.…”
Section: Resultsmentioning
confidence: 99%
“…3 That is, we are interested in political behavior in a setting characterized by nonstatic ambition (Schlesinger 1966;Squire 1988): Given the chance, legislators prefer to "jump" to an executive position rather than continuing in the legislature. This is common in several Latin American countries, notably Argentina, Brazil, and Uruguay (Ames 2001;Chasquetti and Micozzi 2014;Cunow et al 2012;Jones et al 2002;Micozzi 2014aMicozzi , 2014bPereira and Renn o 2013;Power 2000;Samuels 2003). 4 To be sure, nonstatic ambition does not mean that legislative positions are without value.…”
Section: Assumptionsmentioning
confidence: 99%
“…In fact, the Constitution of 1988 and the Rules of the Chamber (Regimento Interno) clearly give the executive sector more legislative and budgetary power than Congress. Cunow et al (2012) have shown that pork-barrel politics was fundamental to assure that the executive branch maintained most of its powers in the 1988 Constitution, accrued during the military dictatorship in Brazil. Using data from the most recent constitutional convention in Brazil, they show that legislators with greater prospects for long careers were actually less likely to support any strengthening of the legislative sector.…”
Section: Conclusion: Implications For Legislative Politics and Professionalizationmentioning
confidence: 99%
“…In fact, werather contra-intuitively -argue that static ambition (i.e., running for reelection) may trump incentives for further professionalization and empowering of the legislative branch if it is mostly defined as a second-best option for political survival. Using data from the Constitutional Convention that approved the new Brazilian Constitution in 1988, Cunow et al (2012) have demonstrated that legislators with greater prospects of long careers in Congress were actually less likely to support the strengthening of the legislative branch. Our results confirm these findings in the post-constitutional setting.…”
Section: Introductionmentioning
confidence: 99%
“…Cunow et al (2012) discuss how the the choice made by the members of the Brazilian constitutional assembly in 1988 were driven by their electoral objectives.…”
mentioning
confidence: 99%